Impacts of digestibility stalls on the welfare of growing bulls - I. Veissier; R. Bellagi; P. Nozière; R. Baumont (Animal)
Diet digestibility and nitrogen balance are essential indicators for studies on ruminant nutrition. Both these indicators are conventionally assessed over 1− to 2-week periods when animals are restrained in so-called digestibility stalls that largely restrict their movements. Here, we aimed to assess the welfare of bulls in digestibility stalls and to check whether stall-related welfare impacts could be limited by shortening the duration of the stay in the stall. Sixteen Charolais bulls accommodated in a large group pen were confined in digestibility stalls for 2 weeks, in two repetitions spaced 2.5 months apart. Urine and faeces were collected daily for 10 days from Day 7 in stalls. From 7 days before the bulls entered the stalls to 7 days after they exited, we measured their feed intake daily and monitored their posture (standing vs lying) and main activity patterns (eating, ruminating, other activity, inactivity) using activity sensors. External lesions (hair losses, wounds) were assessed once a week during the same period. Cortisol was determined in hair from the tail tuft at 3-week intervals from before entering the stalls to after 10 or 15 days in the stalls. Bulls responded to the digestibility stalls by eating lower amounts of feed, spending more time standing or inactive and less time eating or ruminating than when they were in the group pen. The increase in time spent inactive and the decrease in time spent eating were stronger in Repetition 2 than in Repetition 1. The time spent inactive decreased over the first few days in the stalls then increased again over the course of days when urine and faeces were collected. Bulls were more likely to be affected by lesions once they were in the stalls. Hair cortisol increased when the bulls were in the stalls, with a more marked increase after a short stay in Repetition 2. In conclusion, we find definitive evidence that digestibility and nitrogen measurements in digestibility stalls are constraining for animals, and bulls do not appear to habituate to time in the stalls. Confinement in the stalls as well as handling while in the stalls can both have negative welfare impacts.